2022
DOI: 10.3389/fpubh.2022.953155
|View full text |Cite
|
Sign up to set email alerts
|

Association of everyday discrimination with health outcomes among Asian and non-Asian US older adults before and during the COVID-19 pandemic

Abstract: Increases in anti-Asian COVID-19 related discriminatory behaviors have been observed, many of which targeted older adults. Studies demonstrate that racial discrimination is associated with worse health outcomes, including anxiety, depression, and sleep difficulties. No previous studies have examined the impact of day-to-day experiences of discrimination before and during COVID-19 on both Asian and non-Asian older adults within the same sample. We examined whether everyday discrimination was associated with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A study by Levkovich et al (2021) reported that life satisfaction among older adults is not directly related to depression but rather to mediators that increase depression levels. A study conducted in China reported that during a 2-week lockdown period, older adults with increased depression experienced a poor QoL (Tavares, 2022; Zhang et al , 2022b), but they did not report the impact on life satisfaction. While QoL refers to general well-being, but life satisfaction refers to life evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Levkovich et al (2021) reported that life satisfaction among older adults is not directly related to depression but rather to mediators that increase depression levels. A study conducted in China reported that during a 2-week lockdown period, older adults with increased depression experienced a poor QoL (Tavares, 2022; Zhang et al , 2022b), but they did not report the impact on life satisfaction. While QoL refers to general well-being, but life satisfaction refers to life evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The required samples were based on the repeated measures design by measuring each subject four times. Based on a recent study in the USA, a moderate effect size (¼ 0.20) on the change in depression levels in older adults before and after COVID-19 was adopted (Zhang et al, 2022a(Zhang et al, , 2022b. Using the G Ã Power software v3.1.9.7, this study required at least 36 samples that can achieve 80% power and 5% type I error.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations